Peluang dan Tantangan Pustakawan Menghadapi Perkembangan TIK - Muryati, Muryati; Sulistyono, Irwan (Pustakaloka, 2014)
Information and technology has changed all human aspects, including libraries. This condition also changes librarians, this article tries to explore the roles and challenges of librarian in ICT era. The role of lirbrarians in this era are information managers, and information mediators than book keepers, information mediators from many information and resources centre.